Negotiating Gender, Race, and Nationhood in Parenting on Douyin: White Mummy Bloggers in Chinese-Foreign Marriages in China - Xinxin Jiang (Social Media + Society)
This study explores how White mummy bloggers in Chinese-foreign marriages negotiate gender, race, and nationhood through sharenting practices on Douyin, China’s popular short video platform. Drawing on a larger digital ethnography project, it analyzes content from three high-profile accounts featuring White mothers raising mixed-blood children in China. Using a translocational positionality lens, the study examines how these women navigate motherhood as racialized migrants within China’s patriarchal family structures, blend their children’s mixed heritage with Chinese cultural symbols, and engage with national belonging through citizenship. The findings highlight how the performative nature of their parenting allows these bloggers to actively shape their own identities and those of their mixed-blood children, navigating structural constraints and cultural differences while engaging with gendered, racialized, and (trans)national discourses that shape family lives and power relations in transnational households. While doing so, their participation in the attention economy also reveals contradictions—where empowerment and commodification coexist.